The EU’s neoliberal constitutionalism(s) - Guillaume Grégoire (European Law Open)
Beyond their differences, the various currents of neoliberalism share a common legal agenda: economic constitutionalism. From ordoliberal Ordnungspolitik to new classical macroeconomics and public choice, from Hayek’s ‘constitution of liberty’ to Vanberg’s ‘constitutional political economy’, an institutional agenda has emerged around a number of key tenets: enhancing the competition between jurisdictions through (state and international) federalism; safeguarding the competitive functioning of the market through supra-legislative rules; limiting fiscal policies and disciplining public spending through balanced budget rules; neutralising monetary policy through independent and price stability-oriented central banks. These key tenets of neoliberal constitutionalism infuse the three layers of the European economic constitution: the fundamental freedoms of movement pave the way to normative competition between national legislations (microeconomic constitution); competition law guarantees the competitive structure of the market (mesoeconomic constitution); European Economic and Monetary Union implements the rules of budgetary discipline and monetary stability (macroeconomic constitution). This does not imply that the European Union is solely a neoliberal project or that the European Union’s current neoliberal path is irreversible. But it does at least raise questions about the actual room for manoeuvre left by this rigid ‘economic constitution’ to public institutions in dealing with the various current crises.